2018
DOI: 10.1080/03069885.2018.1546378
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring the experience and motivations of UK Samaritan volunteers: “Why do we do it?”

Abstract: A qualitative study exploring the experience and motivations of Samaritan volunteers: "Why do we do it?" Telephone helplines offer a valued service for those in distress. However, little research has explored the experience of helpline volunteers. Through semistructured interviews, in this article we explore the volunteering experiences of nine long-term UK Samaritan volunteers. Interviews were analysed using Interpretive Interactionism. The analysis highlighted that this volunteering impacted participants' ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
2
6
1
Order By: Relevance
“…In line with previous findings, volunteers outlined aspects of the role beneficial to their wellbeing, with respect to personal development and social connectedness (Hector & Aguirre, 2009; Lamb & Cogan, 2016; Mishara & Giroux, 1993; Praetorius & Machtmes, 2005; Smith et al, 2018; Willems et al, 2020). Indeed, the Samaritans community was described as ‘like a family’ and imperative to a supportive environment and successful coping.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In line with previous findings, volunteers outlined aspects of the role beneficial to their wellbeing, with respect to personal development and social connectedness (Hector & Aguirre, 2009; Lamb & Cogan, 2016; Mishara & Giroux, 1993; Praetorius & Machtmes, 2005; Smith et al, 2018; Willems et al, 2020). Indeed, the Samaritans community was described as ‘like a family’ and imperative to a supportive environment and successful coping.…”
Section: Discussionsupporting
confidence: 88%
“…In keeping with prior research, calls were observed to have the potential to elicit a positive or negative emotional response in volunteers, highlighting the spectrum of emotions associated with the role (Kitchingman et al, 2017; Lamb & Cogan, 2016; Middleton et al, 2014; Pollock et al, 2010; Smith et al, 2018; Willems et al, 2020). The volunteers spoke about the changing nature of calls during the pandemic, mirroring trends in other crisis line organisations (Arendt et al, 2020; Batchelor et al, 2021; Joshi et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is confirmed by Haivas et al (2014) who, applying self-determination theory (SDT), recognised the differing needs and therefore motivations of those volunteering. Smith et al (2018) focus on person-centred aspects, such as improving self-esteem, personal wellbeing and life-satisfaction, and Carpenter and Myers (2010) examine altruistic factors, such as wanting to contribute to the wellbeing of others or the community. Gronlund et al (2011) take a wider perspective in examining the influence of national culture on volunteering, while Ling and Chui (2016) concentrate more on the individuals themselves, finding that previous experience of undertaking community or voluntary activities can have a positive influence on volunteering decisions in the future.…”
Section: Introductionmentioning
confidence: 99%